Profile of physical education, sport, and health at Senior High School level - Resi Anadia Shabrina; Ahmad Richard Victorian; Wahyu Indra Bayu (Universitas Sriwijaya, 2025)
Research Problems: Physical Education, Sports, and Health (PESH) are often overlooked compared to other subjects, resulting in some learning objectives not being optimally achieved. Research Objectives: This study aims to analyze the profile of PESH at the Senior High School level, focusing on: (1) the availability of facilities and infrastructure, (2) the availability of PE instructors, (3) the performance of educational institutions in improving PE quality, and (4) achievements and awards over the past year. Methods: The research method used is descriptive quantitative with a survey approach. Data were collected using the Physical Education and Sports Database Instrument developed by the Ministry of Youth and Sports of the Republic of Indonesia. The study was conducted in Senior High Schools across Muara Enim District. Results: The results indicate that, overall, PJOK in these schools falls under the good (B) category. The availability of instructors is rated very good (A), but challenges remain in managing facilities and infrastructure, which require further attention. Additionally, sports achievements need improvement, as some schools only participated in competitions without winning significant awards. Conclusion: Although PESH in Muara Enim District is functioning well, facility maintenance and sports achievement development improvements are necessary to ensure PESH contributes optimally to students' physical development and health.